A combined RNA-seq and whole genome sequencing approach for identification of non-coding pathogenic variants in single families. (3rd February 2020) - Bronstein, Revital; Capowski, Elizabeth E; Mehrotra, Sudeep; Jansen, Alex D; Navarro-Gomez, Daniel; Maher, Mathew; Place, Emily; Sangermano, Riccardo; Bujakowska, Kinga M; Gamm, David M; Pierce, Eric A
Abstract: Inherited retinal degenerations (IRDs) are at the focus of current genetic therapeutic advancements. For a genetic treatment such as gene therapy to be successful, an accurate genetic diagnostic is required. Genetic diagnostics relies on the assessment of the probability that a given DNA variant is pathogenic. Non-coding variants present a unique challenge for such assessments as compared to coding variants. For one, non-coding variants are present at much higher number in the genome than coding variants. In addition, our understanding of the rules that govern the non-coding regions of the genome is less complete than our understanding of the coding regions. Methods that allow for both the identification of candidate non-coding pathogenic variants and their functional validation may help overcome these caveats allowing for a greater number of patients to benefit from advancements in genetic therapeutics. We present here an unbiased approach combining whole genome sequencing (WGS) with patient-induced pluripotent stem cell (iPSC)-derived retinal organoids (ROs) transcriptome analysis. With this approach, we identified and functionally validated a novel pathogenic non-coding variant in a small family with a previously unresolved genetic diagnosis.